Performance of the MITC3+ and MITC4+ shell elements in widely-used benchmark problems. (December 2017) - Ko, Yeongbin; Lee, Youngyu; Lee, Phill-Seung; Bathe, Klaus-Jürgen
Highlights: The performance of the MITC3+ and MITC4+ shell elements is tested. Widely-used benchmark problems are solved in both regular and distorted meshes. The obtained results are compared with those found for some other shell elements. The two shell elements perform consistently well even in distorted meshes. Abstract: Recently, new 3-node and 4-node MITC shell elements, the MITC3+ and MITC4+ elements, have been proposed. The two shell elements were tested through theoretically well-established convergence studies. In this paper we continue to investigate the performance of the MITC3+ and MITC4+ shell elements in relatively simple but widely adopted benchmark problems. To perform these tests as usually done, the predictive capability of the elements is assessed through point-wise convergence of displacements at specific locations of shell structures. The results obtained using the MITC3+ and MITC4+ shell elements are compared with those found for some other shell elements.